Extracurricular Learning For Students in Religious Moderation at Madrasah Aliyah Negeri, South Tangerang City - Sukanti, Lina; Sutarman, Sutarman; Nurislamiah, Siti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the implementation of extracurricular learning and strategies for strengthening religious moderation at Madrasah Aliyah Negeri 1 and MAN Insan Cendikia Serpong, South Tangerang City. The research method used is qualitative with a phenomenological case study approach, focusing on religious moderation as the case to be studied in depth. The conclusion explains efforts to prevent extreme ideologies and religious radicalism. Through persuasive and preventive approaches, it is possible to deter extreme beliefs. The strategy for teaching religious moderation values is implemented by school principals and Islamic Religious Education (PAI) teachers. Islamic spiritual extracurricular learning and PAI development are regularly conducted to guide students in understanding religious diversity. The religious diversity perspective at Madrasah Aliyah Negeri has shown moderate views and acceptance of differences. Although there is still some level of fanaticism among students in practicing their religious teachings, the implementation process remains under control, aligning with both the textual and contextual understanding of religious teachings from the educators, which portray religion as a blessing.